1968
DOI: 10.1113/expphysiol.1968.sp001945
|View full text |Cite
|
Sign up to set email alerts
|

Cholinesterase in the Submaxillary Gland of the Rat After Sympathetic Denervation

Abstract: Cholinesterase activities have been estimated manometrically in submaxillary glands of the rat after postganglionic sympathetic denervation.In denervated glands there is a significant increase of the break down of the two substrates studied, methacholine chloride and benzoylcholine chloride. This finding is considered to support the hypothesis that in the glands there is collateral sprouting of cholinergic fibres after degeneration of adjacent sympathetic neurones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1969
1969
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Increase of total activity in the denervated gland, expressed in percent of that of the contralateral or control gland Nordenfelt (1964Nordenfelt ( , 1965 activity increases gradually in the course of some weeks. It is of interest to note that at the same time an increase occurs in the cholinesterase activity (Nordenfelt 1968). Further, it was found that injections of 6-hydroxydopamine had a similar effect on the enzyme activity in this gland as surgical denervation; the sublingual gland was not affected by the two procedures.…”
Section: Glandmentioning
confidence: 99%
“…Increase of total activity in the denervated gland, expressed in percent of that of the contralateral or control gland Nordenfelt (1964Nordenfelt ( , 1965 activity increases gradually in the course of some weeks. It is of interest to note that at the same time an increase occurs in the cholinesterase activity (Nordenfelt 1968). Further, it was found that injections of 6-hydroxydopamine had a similar effect on the enzyme activity in this gland as surgical denervation; the sublingual gland was not affected by the two procedures.…”
Section: Glandmentioning
confidence: 99%